2021
DOI: 10.4250/jcvi.2020.0138
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound for COVID-19 Pneumonia Patients in the ICU

Abstract: BACKGROUND: There is scarce literature on point-of-care ultrasound (POCUS) assessment characteristics in coronavirus disease 2019 (COVID-19) pneumonia with hypoxic respiratory failure. METHODS: This study was an observational, prospective, single-center study, including adults suspected to have COVID-19 who were transferred to the intensive care unit (ICU). An intensivist in critical care ultrasound performed lung ultrasound (LUS) and echocardiology within 12 hours of patients' admission to the ICU. We calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“… Study Geographical location Incl. criteria Cohort (N) RVD (N) Age (mean) Males (%) ICU (%) HTN (%) T2DM (%) Definition of RVD Outcomes Follow up time (days) Barman (2020) 14 Other COVID-19 patients 90 15 56,4 51 32 35 15 TAPSE ≤ 16 mm Prevalence Bitar (2021) 15 Other COVID-19 patients admitted to ICU 77 9 53* 83 100 26 32 TAPSE < 16 mm, RV S’ < 9.5 cm/s, RV FAC < 35% Prevalence Bleakley (2020) 16 Europe COVID-19 patients underwent mechanical ventilation 84 20 52 74 100 36 22 TAPSE < 17 mm Prevalence Calderon-Esquivel (2020) 17 Other COVID-19 patients admitted to ICU 30 4 59 7 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In early stages of COVID-19 pneumonia, there are focal B-lines, progressing to confluent and multifocal B-lines with subpleural consolidations as the infection advances ( 20 ). Confluent B-lines have been described as “shining white lung” ( 26 ), “torchlight” sign ( 27 ) and “waterfall” sign ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…(5) Several studies have shown that LUS can detect interstitial disease, subpleural consolidations, and respiratory distress of any aetiology, with sensitivity and specificity superior to chest radiography and comparable to CT. (6)(7)(8) Indeed, LUS has already been recommended in past viral pandemics (9) and growing evidence demonstrates its effectiveness in patients with COVID-19, (10) which allows identifying the degree of lung involvement, its course, and the possible association between the initial lung involvement and its prognosis. (11)(12)(13)(14)(15) Our objective was to evaluate the performance of LUS through the lung ultrasound score (LUS score) to determine the severity of pneumonia and the short-term outcomes of patients with COVID-19 admitted to the intensive care unit. We hypothesize that the Lung Ultrasound Score (LUS) correlates with clinical evolution and predicts mortality in critically ill COVID-19 pneumonia patients.…”
Section: Introductionmentioning
confidence: 99%